2013
DOI: 10.1007/s11099-013-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of salicylic acid and ethylene and their effects on some physiological and biochemical parameters in canola plants (Brassica napus L.)

Abstract: Environmental stresses, such as cold, heat, salinity, and drought, induce ethylene production and oxidative stress and cause damage in plants. On the other hand, studies have shown that salicylic acid (SA) induced resistance to environmental stresses in plants. In this research, the effects of ethylene on chlorophyll (Chl), carotenoid (Car), anthocyanin, flavonoids, ascorbic acid, dehydroascorbic acid, total ascorbate, lipid peroxidation, and ethylene production in leaves of canola pretreated with SA were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
3
18
0
1
Order By: Relevance
“…Similar effects of salicylic acid were reported by Hayat et al (2008). Salicylic acid also reduces the lipid peroxidation in plants under drought (Tirani et al, 2013). Ascorbate peroxidase production increases in plants when sprayed with ascorbic acid.…”
Section: Management Strategies For Drought Tolerance In Rapesupporting
confidence: 81%
“…Similar effects of salicylic acid were reported by Hayat et al (2008). Salicylic acid also reduces the lipid peroxidation in plants under drought (Tirani et al, 2013). Ascorbate peroxidase production increases in plants when sprayed with ascorbic acid.…”
Section: Management Strategies For Drought Tolerance In Rapesupporting
confidence: 81%
“…Recently, Khan et al (2014) have shown that the SA improves glycine betaine accumulation and suppresses the ethylene formation in mung bean resulting in improved photosynthesis and growth. It is also reported that ethylene causes oxidative stress and supplementation of SA could improve stress tolerance in canola plants (Tirani et al, 2013). Li et al (1992) have observed that a marked decrease in transcript level occurred in the presence of salicylic acid, which correlated with a strong inhibition in the production of ACC synthase activity in tomato plants.…”
Section: Discussionmentioning
confidence: 94%
“…It has been well documented that exogenous SA may alleviate the damaging effects of various stress factors, and this protection can also be manifested in higher photosynthetic capacity (Horváth et al 2007, Hayat et al 2010, Radwan and Soltan 2012, Sasheva et al 2013, Tirani et al 2013. For example, pre-soaking of seeds in 0.5 mM SA solution for 6 h before sowing substantially decreased harmful effects of cadmium on CO 2 fixation in maize (Krantev et al 2008) or pea ).…”
Section: Effects Of Exogenous Sa On Photosynthetic Processes Under Stmentioning
confidence: 99%